2019
DOI: 10.1556/606.2019.14.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis for traditional yurts using thermal dynamic simulations in Mongolian climate

Abstract: The yurt is one of the ancient living units for the nomadic cultural country. The yurt is a nomadic vernacular architecture, which has been developed for 3000 years. There are 31 counties using the yurt, out of which 13 of them use their traditional yurt around the world. Basically, the yurt was used as residential housings and today, also to some extent, for commercial and touristic purposes under different climates. Analyzing existing literature, as well as scientific publications it is apparent that besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The results of the current field measurements unlock the mystery of how Mongolian nomads managed to create a comfortable thermal environment in extremely cold winters while maintaining their mobility. Although the gers examined in this paper are traditional houses indigenous to Mongolia, similar circular traditional mobile housing exists, or traditionally existed, in various countries including Hungary, Kazakhstan, Kyrgyzstan, and Afghanistan [18]. The results of this study also provide significant insights into the physical environmental factors behind the design of these other nomadic traditional settlements.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results of the current field measurements unlock the mystery of how Mongolian nomads managed to create a comfortable thermal environment in extremely cold winters while maintaining their mobility. Although the gers examined in this paper are traditional houses indigenous to Mongolia, similar circular traditional mobile housing exists, or traditionally existed, in various countries including Hungary, Kazakhstan, Kyrgyzstan, and Afghanistan [18]. The results of this study also provide significant insights into the physical environmental factors behind the design of these other nomadic traditional settlements.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, they plotted the measured data on psychrometric charts and concluded that low and high indoor temperatures and low relative humidity were outside the ISO7730 standard thermal comfort range. Tsovoodavaa and Kistelegdi [18] estimated the heating and cooling energy for nine types of gers, including a current Mongolian ger, as well as similar traditional temporary housing used in other countries based on the building energy simulation approach.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Asian vernacular case studies have been the most assessed in regard to indoor thermal comfort [3,7,[16][17][18][19][20][21][22][23][24][25]8,26,27,[9][10][11][12][13][14][15] (60% of the analysed research), covering a wide variety of humid climate locations, which may be due to not only the prevalence of vernacular architecture at these locations but also the extensive availability of case studies that retain their residential functions. These are then followed at a considerable distance by Portuguese vernacular dwellings [2,5,28], in a Mediterranean hot-dry climate, generally built with local materials such as earth (adobe brick, rammed-earth), stone and wood, and dating back as far as the 17th century, and Iranian vernacular dwellings [29][30][31], mixing earth, brick, and limestone, in a hot-dry and hot-humid tropical climate.…”
Section: Main Features: Case Studies Location Climate and Building Ma...mentioning
confidence: 99%
“…The simulation of vernacular dwellings is a developing research field that allows, inter alia, to obtain long-term performance predictions for a validated model, perform sensitivity and parametric analyses for improving overall performance and comfort, and examine climate change resilience and its impact on thermal comfort. In the past years, it has mainly been applied to assess thermal performance and bioclimatic strategies [22,26,[53][54][55]39,[46][47][48][49][50][51][52], thermal comfort [15,17,38,42,20,23,25,29,[32][33][34][35], energy consumption [23,55], illuminance [56], and computational fluid dynamics [57]. This section highlights the key findings stemming from the analysis of the most relevant recently published research on the simulation of vernacular dwellings for thermal performance and comfort analysis, amounting to 26 publications.…”
Section: Modelling Vernacular Dwellings: Analysis Of Researchmentioning
confidence: 99%
“…Currently, the dynamic thermal simulation of these types of dwellings is an expanding research field with extensive potential for, inter alia, obtaining long-term performance predictions, performing sensitivity and parametric analyses, and examining climate change resilience and its impact on thermal comfort [3,4]. Since the research interest on this topic peaked in 2014, 26 studies have been published on modelling vernacular dwellings , of which 19 focus on thermal comfort evaluation [6,11,[14][15][16][17]21,22,[35][36][37][38][39][40][41][42][43][44][45] by combining simulation and in situ monitoring, with EnergyPlus via the DesignBuilder interface being by far the most employed [4]. Moreover, a systematic review of vernacular dwellings' climate responsiveness was recently published, confirming the research trend of coupling fieldwork with simulation for evaluating climate responsiveness and the effectiveness of strategies, with EnergyPlus via DesignBuilder being the main simulation software, followed by Ecotect, Phoenics and eQuest [46].…”
mentioning
confidence: 99%